Language Maintenance melalui Implementasi Kebijakan Pengembangan Bahasa Bali di Kota Denpasar - I Putu Ariana; Made Bayu Anantawijaya Nala; I Made Agus Atseriyawan Hadi Sutresna (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
Balinese langauge as a core element of Balinese culture, faces challenges amidst urbanization and globalization, particularly in Denpasar City. This study analyzes the implementation of Balinese language development policies based on regulations such as Bali Provincial Regulation No. 1 of 2018 and Bali Governor Regulation No. 80 of 2018. A descriptive qualitative approach is used through document analysis and literature review. The results demonstrate the success of programs such as Balinese Language Month in increasing community participation, although challenges such as declining language use among young people remain. The discussion emphasizes the need for digital and family integration for revitalization, with a focus on language maintenance aspects using Fishman's sociolinguistic theory that highlights intergenerational transmission and strengthening the domain of language use. The conclusion recommends strengthening policies for the sustainability of Balinese language, including a synergistic approach between the government, communities, and educational institutions. This study contributes to the understanding of regional language maintenance in urban contexts, with implications for national policy in Indonesia.